Type studies on two Paxillus species (Paxillaceae, Boletales) described from China - Liu, Li-Rong; Wang, Geng-Shen; Jia, Liu-Kun; Kang, Ju-Qing; Yang, Zhu-Liang; Li, Yan-Chun (Phytotaxa, 2022)
Types and recently collected samples of two Paxillus species namely P. rhytidophyllus and P. yunnanensis, originally described from southwestern China, were critically restudied based on morphology and molecular phylogenetic data of DNA sequences from the large subunit of the nuclear ribosomal RNA (nrLSU), the nuclear ribosomal internal transcribed spacer (ITS), and the translation elongation factor 1-α (tef1-α). The results showed that these two species belong to Boletinellus and Tricholomopsis, respectively. Thus, two new combinations, Boletinellus rhytidophyllus and Tricholomopsis yunnanensis are proposed. Boletinellus rhytidophyllus is characterized by a deeply decurrent and shallow hymenophore which is poroid-lamellate to alveolate, slightly thick-walled (0.6–1 μm) basidiospores, occasionally 2- to 4-spored basidia, rare or infrequent hymenial cystidia, and a trichodermal pileipellis. Tricholomopsis yunnanensis is characterized by a convex pileus densely covered by red-violet to red-brown fibrillose squamules, a yellowish stipe sparsely covered with red to red-brown fibrillose squamules, subglobose to broadly ellipsoid basidiospores, prominent large cheilocystidia measuring 60–195 × 11–39 μm, and a palisadic pileipellis. New descriptions and line drawings of these two species and their comparisons with allied taxa are presented.